Communicative and cognitive abilities of deaf students: protocol design - Rodríguez Hernández, Yenny; Muñoz Vilugrón, Karina Andrea; Sastre, Carmen Obdulia (Revista de Investigación en Logopedia, 2019)
Collaborative work between teachers and speech therapists in the classroom is a valid strategy to promote communication and the cognitive processes in deaf children. The growing number of deaf students in regular education brings several challenges. One of them, instruments’ use to identify and describe different aspects to improve in classrooms. The following article introduces the results of an interdisciplinary work focused on the design of two evaluation protocols (communication and cognitive processes) to be used in the classroom with deaf students. The descriptive study contemplated three phases (instrument design, validation by experts, and piloting). 12 professionals participated in the first phase while 5 teachers and 12 deaf students participated in the piloting. The results showed that the dimensions, the items and the scales of each protocol were valid to register and characterize the behaviors studied. They also showed the objectivity and functionality of each instrument in order to describe the observed behaviors. The study concluded that the two protocols can be used in the school context for the purposes for which they were created and it recommends expanding its application to other Chilean and Colombian cities.
Keywords: deaf students; classroom; communication; cognitive processes; teachers